2015
DOI: 10.1097/scs.0000000000002018
|View full text |Cite
|
Sign up to set email alerts
|

Occlusal Relations in Patients With Scaphocephaly

Abstract: Scaphocephaly results from a premature fusion of the sagittal suture. Usually, cranial vault corrective surgery is performed during the first year of life. There is currently no scientific data regarding occlusion of scaphocephalic patients, or the potential effect of craniovault surgery on the occlusion. The aims were to describe occlusion in scaphocephalic patients and compare with a general pediatric population, and to compare the difference in occlusion of surgically versus unoperated treated scaphocephali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…Children affected with non‐syndromic single suture synostosis show maxillary asymmetry, class II occlusion and occlusal canting 28–30 . Scaphocephalic craniosynostosis results in retrognathic mandibles, labially inclined lower incisors and slightly more cross‐bite occlusion than the normal population 31,32 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children affected with non‐syndromic single suture synostosis show maxillary asymmetry, class II occlusion and occlusal canting 28–30 . Scaphocephalic craniosynostosis results in retrognathic mandibles, labially inclined lower incisors and slightly more cross‐bite occlusion than the normal population 31,32 …”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] Scaphocephalic craniosynostosis results in retrognathic mandibles, labially inclined lower incisors and slightly more cross-bite occlusion than the normal population. 31,32 Posterior plagiocephaly causes asymmetry of the cranium, cranial base, maxilla and mandibula, and it may also cause dental occlusal problems. Presumptions that plagiocephaly influences the jaws and dental occlusion are based on the fact that plagiocephaly has asymmetric effects on the cranial base and, consequently, on the glenoid fossa.…”
Section: Ta B L Ementioning
confidence: 99%
“…Patients with isolated craniosynostosis require multidisciplinary care for treating the craniosynostosis itself and the other health issues these patients may present with (Vargervik et al, 2012). Dental and orthodontic care should be considered important in patients with isolated craniosynostosis, with studies revealing possible increased need for care in the dentition and occlusion (Mustafa et al, 2001; Dalben et al, 2006; Pelo et al, 2011; Heliövaara et al, 2015; Lebuis et al, 2015). Studies have reported higher decayed, missing, or filled teeth and plaque scores in patients with craniosynostosis, putting more pressure on delivering enhanced dental follow-up programs and aiding in achieving proper oral hygiene (Mustafa et al, 2001; Dalben et al, 2006; Vargervik et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Similar gene networks regulate skull and tooth morphogenesis (Yuan and Chai, 2019). Occlusal characteristics are been studied in patients with isolated craniosynostosis, proposing interesting results in alterations in craniofacial growth patterns (Pelo et al, 2011; Heliövaara et al, 2015; Lebuis et al, 2015). Retrognathic mandibles in patients with scaphocephaly and dentoskeletal asymmetry occurring in tandem with coronal synostosis have been reported (Pelo et al, 2011; Heliövaara et al, 2015; Lebuis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation